2017
DOI: 10.1073/pnas.1621067114
|View full text |Cite
|
Sign up to set email alerts
|

Conformity does not perpetuate suboptimal traditions in a wild population of songbirds

Abstract: Social learning is important to the life history of many animals, helping individuals to acquire new adaptive behavior. However despite long-running debate, it remains an open question whether a reliance on social learning can also lead to mismatched or maladaptive behavior. In a previous study, we experimentally induced traditions for opening a bidirectional door puzzle box in replicate subpopulations of the great tit Parus major. Individuals were conformist social learners, resulting in stable cultural behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
123
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(133 citation statements)
references
References 44 publications
9
123
1
Order By: Relevance
“…However, innovations that are effortful and rare when they first appear within a generation can become effortlessly and widely adopted by the next generation. In fact, among nonhuman animals, cultural innovations are often first produced, adopted, and spread by juveniles (55)(56)(57)(58).…”
mentioning
confidence: 99%
“…However, innovations that are effortful and rare when they first appear within a generation can become effortlessly and widely adopted by the next generation. In fact, among nonhuman animals, cultural innovations are often first produced, adopted, and spread by juveniles (55)(56)(57)(58).…”
mentioning
confidence: 99%
“…A striking case is the high-fidelity spread of alternative foraging behaviors experimentally seeded in substantial communities of great tits (40). Here, Aplin et al (41) show that these behaviors will evolve adaptively as payoffs change, and the authors present evidence that this occurs through an intriguing combination of conformist social learning and payoffsensitive individual learning.…”
Section: The Discovery Of Widespread Animal Culturementioning
confidence: 89%
“…Hundreds of laboratory experimental studies have demonstrated social learning and transmission in a wide variety of animals. Social learning is now extensively documented in mammals (29), with a particular intensity of research studies in primates (30)(31)(32)(33) and cetaceans (34)(35)(36)(37), in birds (38)(39)(40)(41), in fish (42), and in insects (43,44). The fact that social learning has been shown to play important roles spanning multiple functional contexts (25)(26)(27)(28) suggests that many animals are not simply acquiring one or a few behavioral patterns socially, but rather that social learning is central to their acquisition of adaptive behavior.…”
Section: The Discovery Of Widespread Animal Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Conformity can be conceptualized in different ways (Van Leeuwen et al, 2015;Whiten and van de Waal, 2016a), from copying the majority, to copying a new behavioral variant while abandoning a personal preference for a previously acquired behavioral variant, to not only copying the majority but doing so with a disproportionate probability. Empirical evidence for such a disproportionate tendency is scarce in humans (Acerbi et al, 2016) and also among animals (Aplin et al, 2017). However, there is increasing evidence in primates for the other forms of conformity.…”
Section: Conformitymentioning
confidence: 99%